Enclosure Then and Now: Rural Schools and Communities in the Wake of Market-Driven Agriculture - Paul Theobald; Ronald S. Rochon (Journal of Research in Rural Education, 2006)
The following is an historically-based analysis of a new phenomenon affecting rural schools and communities: animal confinement operations. A contrast is made between "enclosure" as it unfolded in England a few centuries ago and the way animal concentration units constitute a second, "modern" form of enclosure today. In both instances, as this essay demonstrates, rural populations have suffered markedly.